DNA methylation: a permissive mark in memory formation and maintenance - Oliveira, Ana (Learning & memory, 2016)
DNA methylation was traditionally viewed as a static mechanism required during cell fate determination. This view has been challenged and it is now accepted that DNA methylation is involved in the regulation of genomic responses in mature neurons, particularly in cognitive functions. The evidence for a role of DNA methylation in memory formation and maintenance comes from the increasing number of studies that have assessed the effects of manipulation of DNA methylation modifiers in the ability to form and maintain memories. Moreover, insights from genome-wide analyses of the hippocampal DNA methylation status after neuronal activity show that DNA methylation is dynamically regulated. Despite all the experimental evidence, we are still far from having a clear picture of how DNA methylation regulates long-term adaptations. This review aims on one hand to describe the findings that led to the confirmation of DNA methylation as an important player in memory formation. On the other hand, it tries to integrate these discoveries into the current views of how memories are formed and maintained.
Gesehen am 03.07.2020